Trust dynamics in acquisitions: A case survey - Stahl, Günter K.; Larsson, Rikard; Kremershof, Ina; Sitkin, Sim B. (Human Resource Management, 2011)
AbstractDrawing on the organizational trust literature and research on postmerger integration, the authors develop a model that conceptually synthesizes the antecedents and consequences of trust in acquired organizations. The model proposes that the acquiring and target firms' relationship history, the interfirm distance, and the acquirer's integration approach will affect target firm member trust in the acquiring firm's management. Target firm member trust, in turn, may influence several sociocultural integration outcomes as well as postacquisition performance. The results of a case survey suggest that certain aspects of the relationship history and interfirm distance, such as the firms' collaboration history and preacquisition performance differences, are poor predictors of trust, whereas integration process variables, such as speed of integration, communication quality, and acquirer multiculturalism are major factors influencing trust. The implications for postmerger integration research and practice are discussed. © 2011 Wiley Periodicals, Inc.